Towards a Sustainable Digital Future: Exploring AI, Legal Frameworks, and Environmental Transformations in the Post-COVID Era? - Kapartziani, Chrysoula (European Scientific Journal, ESJ, 2025)
This research paper examines the environmental, legal, and governance implications of digitalization, focusing on the intersection of software engineering, sustainability, and accountability. As digital systems and Artificial Intelligence (AI) become increasingly embedded in society, their environmental footprint and regulatory challenges demand urgent attention. Drawing upon theories from scholars such as Beck on modernity and Haraway on the interconnected digital era, this study investigates how digitalization reshapes governance structures and sustainability efforts. The research addresses the growing environmental impact of AI and digital technologies, identifying gaps in existing legal and governance frameworks that fail to account for sustainability. The key objectives are to assess the energy consumption and ecological footprint of digitalization, analyze the perspectives of software professionals on sustainability, and propose accountability mechanisms that integrate environmental governance with software engineering practices. Methodologically, this study combines a literature review with qualitative research, including interviews with software professionals, to explore how sustainability considerations are—or are not—integrated into software development. The research highlights the lack of systematic approaches in current governance models and the absence of clear regulatory oversight regarding AI’s environmental impact. Acknowledging the limitations of available data and the challenges of regulatory harmonization, this study underscores the need for interdisciplinary collaboration between technologists, policymakers, and environmental researchers. Key findings emphasize the necessity of incorporating accountability into sustainability frameworks to foster effective transformations. The research examines software engineering practices, particularly regarding energy efficiency, carbon footprints, and the broader environmental consequences of digitalization. Using the concept of co-production, this study highlights the interconnectedness of technological advancements and environmental governance. Strategies based on Science and Technology Studies (STS) are proposed to guide the socio-technical transformation required for sustainability. To address these challenges, the study recommends the implementation of comprehensive legal frameworks, the adoption of sustainability metrics within software engineering, and the promotion of knowledge-sharing initiatives that enhance digital governance. By emphasizing the role of education, legal culture, and governance mechanisms, this research aims to contribute to a paradigm shift toward a more accountable and sustainable digital future.